Comparison of distributed and Centralized control for partial shading in PV parallel based on Particle Swarm Optimization Algorithm - Jumpasri, Nattawat; Pinsuntia, Kittapas; Woranetsuttikul, Kaweepoj; Nilsakorn, Taywin; Khan-Ngern, Werachet (My University, 2014)
This paper presents the comparison of Distributed Control and Centralized Control for partial shading in PV parallel based on the Particle Swarm Optimization Algorithm. The distributed control is the connection of PV 1 panel with 1 MPPT and the centralized control is the connection of many PV panels with 1 MPPT. Both methods have difference advantage, efficiency, cost and maintenance. The simulation of both methods made in Powersim and Matlab Simulink. The analysis and conclusion were included.
Keywords: Centralized control; Distributed control; MPPT; PSO; PV; shading